Transporte eletrônico em nanofios de SnO2 dopado com Sb: transição metal-isolante induzida pela dopagem e fotocondutividade persistente - Costa, Ivani Meneses (2019)
In this work we studied the structural, optical and electronic transport properties of intrinsic and doped SnO2 nanowires with different concentrations of antimony (Sb) grown by the Vapor-Liquid-Solid mechanism (VLS). Results from X-ray diffraction (XRD) combined with Rietveld refinement, indicated the formation of single phase samples corresponding to the tetragonal Rutile structure of SnO2 belonging to the P42/mnm spatial group. Raman spectroscopy data also indicated the formation of rutile phase corroborating the XRD measurements. The appearance of inactive vibrational modes (242 and 284 cm-1) only for the doped samples was attributed to the effects of disorder. XPS analyzes confirmed the presence of Sb in doped samples. The presence of Sb was evidenced by the superposition of the O1s and Sb3d regions and only one oxidation state (Sb5+) was detected. Absorbance spectra indicated that the doped samples exhibited an energy gap (3,40 - 3,66 eV) greater than that for pure samples (3,3 eV). This result is consistent with the Burstein-Moss model which describes the shift of the absorption limit due to the increase of the density of charged carriers. From photoluminescence spectra it was observed that the SnO2 samples presented three emission peaks related to oxygen vacancies, V0+ (red), (V0+)iso (yellow/orange) and V0++ (green). The green emitter center was actived only below T = 100 K. ATO samples showed only two emission peaks: the red emitting center (V0+) also present in pure samples and a doping-related blue-violet emitter center located at 2,58 - 2,84 eV. Temperature dependent resistivity data showed that the SnO2 samples presented a typical behavior of a semiconductor material, while ATO samples presented a transition from an insulating state (dR/dT < 0) to a metallic one (dR/dT > 0) around 90 - 170 K depending on the doping level. The semiconductor phase was characterized by two electron conduction mechanisms: thermal activation and variable range hopping (VRH). The metal phase was characterized by electron-electron and electron-phonon scatterings. The electron-phonon process was predominant at high temperatures leading to the calculation of the Debye temperature of the samples (ΘD = 602 - 657 K). All doped samples were characterized by doping levels above the Mott limit (ncMott = 6,7 x 10^23 m-3) thus satisfying the Mott criterion for observation of the metal-insulator transition based on the electron-electron interaction. In addition, it was observed that both the nanowire device and the SnO2 nanowire network device exhibit persistent photoconductivity (PPC) which is directly related to the presence of oxygen vacancies. For the nanowire network, the PPC effect was only observed under vacuum conditions, since under room environment conditions the nanowire-nanowire junctions strongly affect the electric current through the device. However, only for the single nanowire device we observed PPC also under high temperatures. The energy level attributed to the emitting center V0++ can be seen as responsible for the anomalous behavior in the low temperature resistivity curves (T < 100 K).